2016
DOI: 10.1080/09513590.2016.1214258
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin levels in idiopathic hypogonadotropic hypogonadism diagnosed male patients and its relation with glucose-insulin dynamic

Abstract: Male hypogonadism is defined as the deficiency of testosterone or sperm production synthesized by testicles or the deficiency of both. The reasons for hypogonadism may be primary, meaning testicular or secondary, meaning hypothalamohypophyseal. In hypogonadotropic hypogonadism (HH), there is indeficiency in gonadotropic hormones due to hypothalamic or hypophyseal reasons. Gonadotropin-releasing hormone (GnRH) is an important stimulant in releasing follicular stimulant hormone (FSH), mainly luteinizing hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The deficiency of INS reduces kisspeptin protein expression in the hypothalamus, resulting in decrease in GnRH secretion leading to HH. Supplementation of INS can correct the abnormality of GnRH (27). Compared with the peripheral gonads, abnormal levels of INS have a greater impact on hypothalamus and pituitary.…”
Section: Role Of Hypothalamic Pituitary Gonadal Axis In the Reproduction Of Diabetic Menmentioning
confidence: 99%
“…The deficiency of INS reduces kisspeptin protein expression in the hypothalamus, resulting in decrease in GnRH secretion leading to HH. Supplementation of INS can correct the abnormality of GnRH (27). Compared with the peripheral gonads, abnormal levels of INS have a greater impact on hypothalamus and pituitary.…”
Section: Role Of Hypothalamic Pituitary Gonadal Axis In the Reproduction Of Diabetic Menmentioning
confidence: 99%
“…Moreover, this experimental study on an animal model has proved that GPR54 − / − mice could not respond with the increase in GnRH secretion to the supply of kisspeptin [ 17 ]. Further studies confirmed the hypothesis that kisspeptin could regulate the hypothalamus-pituitary-gonad (HPG) axis, and the mutation of KISS-1R is responsible for the development of idiopathic hypogonadotropic hypogonadism [ 18 ].…”
Section: Introductionmentioning
confidence: 76%
“…19 20 21 22 23 24 25 26 Here, this study describes the molecular mimicry and the immunologic cross-reactive potential between SARS-CoV-2 and KISSR, alterations of which are responsible for hypogonadotropic hypogonadism syndrome. 3 4…”
Section: Discussionmentioning
confidence: 99%
“…1 As reviewed by Szydełko-Gorzkowicz et al, 2 KISS1 and KISSR participate in different biological processes in that KISS1 plays an essential role in governing pubertal onset and human reproduction, while alterations of KISSR are responsible for the development of hypogonadotropic hypogonadism syndrome that includes dysfunction of fertility, absent or incomplete sexual maturation, and puberty disorders. 3 4…”
Section: Introductionmentioning
confidence: 99%